MGNREGA-The Public Policy in India: An Empowerment Analysis - Chakrobarty , Arindam (Economic Journal of Development Issues, 2024)
Empowerment of women is the process of challenging the existing power relations and gaining control over the source of power. MGNREGA, the flagship programme of India has made room for the rural women for challenging the power relations within the households as well as in the society. Thus, this study seeks to analyze the impact of the MGNREGA program on women’s empowerment. The survey was conducted at the household level in Nadia District, West Bengal, India, during 2016-17. Four out of the 17 community development blocks were selected for the study, and a total of approximately 500 households engaged in MGNREGA works were randomly chosen from these gram panchayats. The findings reveal that higher work participation under MGNREGA has empowered women to engage more confidently and actively in Gram Sabha meetings. The study highlights a unique interrelationship between work participation and active involvement in decision-making processes under the scheme.